(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the advantages of three days of face-to-face class in terms of academic performance, extra-curricular activities, and improving social skills of grade 12 HUMSS students. The result of this study reveals that the three days of face-to-face classes have the advantage to grade 12 HUMSS students in terms of their academic performance, extra-curricular activities, and improving social skills. This study recommended that face-to-face classes are advantageous if the students are using strategies to review their lessons and use the library to study. Also, the students should be sociable and cooperative when it comes to schoolwork or activities. Lastly, the students should be wise in choosing their circle of friends. They should befriend the students who care about their academics and those who can make them feel a sense of belonging.